Potensi dan Tantangan Pengembangan Kawasan Kota Lama Semarang sebagai Destinasi Wisata dengan Pendekatan Smart Tourism - Noval Pinasthika; Wisnu Pradoto (Jurusan Perencanaan Wilayah dan Kota, 2018)
Semarang City Old Town is one of the tourist icon of Semarang City. The interesting thing about the Old Town area of Semarang is the historic building which makes it dubbed as one of the World Heritage City. But the city of Semarang tourism is considered still less attractive than the city of Solo or Yogyakarta. At the same time, Semarang City won an award from Indonesia Smart Nation Award (ISNA) in 2015 with the smart city's highest index. Implementation of the concept of integrated smart city in Semarang City will certainly encourage the Old City of Semarang to apply the concept of intelligent tourism. This study aims to determine the potential and challenges of the concept of intelligent tourism applied in the Old Town area of Semarang. The method used is descriptive quantitative with the analysis technique of Service Quality and Importance Performance Analysis (IPA). The results of this study indicate that the Old Town area of Semarang still has many challenges because of the 13 important elements of smart tourism The Old City area of Semarang only has 5 elements. The elements are those that have not yet optimal performance levels.